Investigation of Fluid Excitation Forces Induced by Cylindrical and Conical Whirls in a Long Annular Seal Using Transient CFD Methods - Li, Fengqin; Zhai, Lulu; Cui, Baoling; Zhu, Zuchao; Guo, Jia (Frontiers in Energy Research, 2022)
Annular seals can induce fluid excitation forces that severely affect the stability of the pump rotor systems. In this paper, a transient computational fluid dynamic (CFD) method with a mesh deformation technique is used to study the fluid excitation forces generated on the long annular seal caused by cylindrical whirls and conical whirls. The reliability of the method is verified by comparing the simulation results with the experimental results. The whirl motion, composed of cylindrical and conical whirls, is realized by the phase difference between the whirl movements at the annular seal inlet and outlet, and the effects of the phase difference and inlet preswirl on the fluid excitation forces are studied numerically. The results show that the fluid excitation forces significantly depend on the phase difference of the rotor whirl movement, and tangential force acts as a stabilizing force only when the phase difference approaches 45º. The tangential forces of the cylindrical whirl, the conical whirl and the form of cylindrical and conical combined whirl are sensitive to inlet preswirl, while the effect of inlet preswirl on the radial forces becomes obvious only when the rotor whirls in the form of combined whirls.